A systematic data screening strategy for comprehensive characterization of chemical components in Suan-Zao-Ren decoction and their metabolic profiles in the plasma and brain of rats using ultra high performance liquid chromatography quadrupole time-of-flight mass spectrometry. Issue 43 (21st October 2019) - Du, Yiyang; Wu, Bo; Xiao, Feng; Yan, Tingxu; Jia, Ying; Bi, Kaishun; He, Bosai
Abstract : Suan-Zao-Ren decoction is a classic traditional Chinese medicinal prescription, which has been used in the clinical treatment of insomnia and anxiety for thousands of years. Abstract : Suan-Zao-Ren decoction is a classic traditional Chinese medicinal prescription, which has been used in the clinical treatment of insomnia and anxiety for thousands of years. In order to explore the pharmacological material basis of this decoction, its various components and their metabolic pathways in the serum and brain of rats based on ultra high performance liquid chromatography quadrupole time-of-flight mass spectrometry coupled with data mining were investigated for the first time in this research. Overall, a total of 110 components were identified or tentatively identified from the Suan-Zao-Ren decoction. Also, 35 prototype components and 36 metabolites were detected in rat plasma, whereas 18 prototype components and 4 metabolites were detected in rat brains. The absorbed components that could cross the blood–brain barrier to the brain were first observed after the oral administration of the Suan-Zao-Ren decoction. The metabolic pathways of the potential bioactive components mainly involved hydrolysis, sulfate conjugation, glucuronide conjugation and other metabolic reactions. The results of our work demonstrate a well-developed method for compositional characterization both in vitro and in vivo, which can provide a detailed chemical basis for the subsequent pharmacological mechanism research.